2010
DOI: 10.1021/jp107391x
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of the Mechanism of Valence Tautomerism in Cobalt Complexes

Abstract: Valence tautomerism is studied in the [Co(II-HS)(sq)(2)(bpy)]/[Co(III-LS)(sq)(cat)(bpy)] mononuclear cobalt complex by using DFT methods (HS, high spin; LS, low spin; cat, catecholate; sq, semiquinone; bpy, 2,2'-bipyridine). Calculations at the B3LYP* level of theory reproduce well the energy gap between the Co(II-HS) and Co(III-LS) forms giving an energy gap of 4.4 kcal/mol, which is comparable to the experimental value of 8.9 kcal/mol. Potential energy surfaces and crossing seams of the electronic states of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 64 publications
3
37
0
Order By: Relevance
“…Recently, it was reported that the relaxation mechanism between the HS state of Co II and the LS state of Co III , which is observed in a similar valence tautomeric compound, [Co(sq) 2 (bpy)] (sq = semiquinone; bpy = 2,2Ј-bipyridine), was expected to be a one-step mechanism, according to the energy of the three spin states and the crossing points obtained by the ab initio molecular orbital calculations with the DFT method. [25] In our results that support a two-step mechanism, the electrons transferred from the dhbq ligand go to the next state, which is the transient LS state of Co II . Since this transient state is a low-lying state with a short lifetime, it may be out www.eurjic.orgof the scope of the accuracy of the ab initio DFT calculation reported previously.…”
Section: Relaxation Processsupporting
confidence: 66%
“…Recently, it was reported that the relaxation mechanism between the HS state of Co II and the LS state of Co III , which is observed in a similar valence tautomeric compound, [Co(sq) 2 (bpy)] (sq = semiquinone; bpy = 2,2Ј-bipyridine), was expected to be a one-step mechanism, according to the energy of the three spin states and the crossing points obtained by the ab initio molecular orbital calculations with the DFT method. [25] In our results that support a two-step mechanism, the electrons transferred from the dhbq ligand go to the next state, which is the transient LS state of Co II . Since this transient state is a low-lying state with a short lifetime, it may be out www.eurjic.orgof the scope of the accuracy of the ab initio DFT calculation reported previously.…”
Section: Relaxation Processsupporting
confidence: 66%
“…The density functional theory (DFT) calculations were performed using the Gaussian 09 program package with the standard 6‐311++G(d,p) basis set including diffuse and polarization functions at all atoms. As it was shown in the previously published works, depending on the central ion, the type of the magnetic bistability mechanism resulting in switching the magnetic characteristics, and the presence of charge of the complex, the best agreement with the experiment is achieved when using hybrid functionals UB3LYP* or UTPSSh . Due to the electroneutrality of the modeled compounds, all the calculations were performed with the use of modified UB3LYP functional—UB3LYP* .…”
Section: Methodsmentioning
confidence: 89%
“…Similar to spin‐crossover metal complexes, calculation of relative energies for different electronic states of VT species is rather inaccurate. However, recent theoretical works on VT complexes showed that OPBE36 and B3LYP*37 functionals produce satisfactory results 38. 39 Therefore, we optimized the geometries of 1 and 2 , as well that of reference complex 3 (Scheme ) in different electronic states with the OPBE functional and calculated their relative energies.…”
Section: Resultsmentioning
confidence: 99%